(untitled) (Nepalese Journal of Management Research, 2021)
The purpose of this paper is to study the consumer buying behavior towards cosmetics. This study primarily focuses on various factors like age, occupation; marital status and educations have positive influence towards cosmetic products. Primary data were used in research. Questionnaire of survey included five point likert scales. 110 completed questionnaires were returned and then 100 valid were analyzed by using ANOVA, mean and standard deviation. Surprisingly in Chitwan, the factor income does not have any influence on the attitude towards cosmetic products among the consumers understudy. People consider quality as the most important factor to purchase cosmetics. The findings may be used to marketers to design marketing strategy for cosmetics.